Icts diffusion trajectories and economic development – An empirical evidence for 46 developing countries - Ewa Lechman (Gdańsk University of Technology, Faculty of Management and Economics, 2013)
In economic theory, technology is treated as crucial factor contributing significantly to economic development. In seminal works of Schumpeter [1934, 1947], Baumol [1986], Gerschenkron [1962] or Abramovitz [1986], the emphasis on the role of technological progress in process of economic development is put extensively. Along with the previous, there emerged theoretical and empirical works on technology diffusion (i.e. Rogers 1962, Geroski 2000), where the dynamics of the process is considered. Temporarily, the spread on new information and communication technologies (ICTs) is massive. The objectives of the study are twofold. Using panel data we analyze the diffusion trajectories of ICTs in developing countries, and we assess the dynamics of the process. Secondly, we hypothesize on existence quantitative links between ICTs adoption and economic development. The time framework is set for period 2000-2011. Statistical data are derived from World Telecommunication/ICT Indicators Database 2012, World Development Indicators 2013 and Human Development Report 2013.
Keywords: O10; O33; O57; 330; ICTs; diffusion; economic development; developing countries; S-shaped curve